Family health program: reviewing actions developed in the attendance to the woman’s health - Girlene Maria Magalhães Cavalcante de Alencar; Thereza Maria Magalhães Moreira; Enedina Soares (Rev Rene)
This study was aimed to evaluate the actions of attention of health of the women in the Family Health Program (PSF) of São Francisco, district of Pedra Branca – Ceará, among 1998-1999. The sample was 251 women in fertile age assisted in the program in that time. The data of 1999 show increase of the number of consultations of family planning (of nursing and of doctor), of the number of pregnant registred and vaccinated and of the index of pregnant woman with prenatal up-to-date. Relative improvement is observed in attention to woman’s health by control of the prenatal begun in the first trimester of gestation and by the control of pregnant woman under 20 year-old, also in the detection of cases of brenst cancer and womb cancer. It’s considered that the actions have gotten more progress, and that the establishment of a link between PSF group and community have helped to the improvement of the actions made in that district.